Fragmentary mentality of Donbas: towers of besieged town - Turenko, Oleh (Skhid, 2015)
The Russian-Soviet fundamentals of mentality of present-day Donbas inhabitants are reviewed, which the author describes as affective fragmentary mentality. Its key features are historical versatility of values, sharp internal contradiction, entwinement of archaic heathen and Christian ideas, strong influence of myth and fairytale archetypes as well as incapability to accept positive ideas of western civilization at large. A number of attempts to modernize the country and accept the educational heritage of Europe have not changed Russian-Soviet mentality, the latter taking a disguising and imitational, externally aggressive and internally confined form. Further still, Russian-Soviet mentality preserved its local microcosm - the archaic peasant world. It produced justification to its slavish and serf state as well as tellurgic principles of justice and developed crafty mechanisms for preservation of its identity. That said, mentality of the ruling class also remained unchanged - having escaped European education, it remained to be haughty parasiting community which complied with bureaucratic and clientelist values. Such stagnation trends existed in the USSR and in the Donbas territory during the years of independence of Ukraine. The post-Soviet people of the Donbas could not create social space for self-development, the majority lacking adaptation mechanisms for the purpose and motivations for acquiring modern skills. Mental stagnation resulted in refusal to perceive the present day and its reality. Donbas mentality has therefore developed no positive mechanisms for adaptation to new reality of life and refused modern meanings of life, by sinking into archaic archetypes of the Russian-Soviet past.